Severe case of Streptococcus suis meningitis in Bali Mandara Hospital: a case report - Saputra, I Wayan Agus Gede Manik; Triatmoko, Indira Chadijah; Widarmawan, I Gede Eka; Hermawan, I Gede; Adi, Putu Dwi (Journal of Clinical Microbiology and Infectious Diseases, 2023)
Background: Streptococcus suis meningitis (SSM) is one of the zoonotic disease that can cause serious illness in humans.  The major risk factor in many cases of SSM is associated with pig husbandry and consuming undercooked pork products. In Indonesia, especially in Bali, the cases of this acute bacterial meningitis has been strongly correlated with consuming Balinese traditional food called “red lawar”, a mixture of raw pork, fresh pork blood and traditional Balinese herbs. This study aims to report a case of SSM in Bali Mandara Hospital. Case description: A 63-year-old man admitted to the Emergency Department because of a decrease in consciousness (Glasgow coma scale 3/15).  This patient was transferred from a private hospital with septic shock and suspicious to acute bacterial meningitis.  He  had other related  symptoms like fever, headache, and cough since two days prior to admission. He also had a history of consuming “red lawar” 2 days before the symptoms appeared.  Laboratory findings from cerebrospinal fluid analysis and septic marker indicate the patient had bacterial meningitis. The patient was initially started by Meropenem due to his septic shock.  The broad spectrum antibiotics were then de-escalate to Ceftriaxone once the culture and sensitivity test completed and yielded Streptococcus suis.  The course of Ceftriaxone as definitive therapy has been administered for 14 days and showed clinical improvement without specific sequelae related to SSM infection like hearing loss. Conclusion: Severe meningitis e.c Streptococcus suis leading to septic shock is a life threatening health condition. Adequate antibiotic therapy and multidisciplinary approach can reduce mortality and morbidity of this case.